Towards the implementation of sustainable development goals in Nigeria: Maximizing the influence of religious leaders - Akinloye, Idowu A. (Stellenbosch theological journal, 2018)
The limited scope of the Millennium Development Goals (MDGs) and the failure of the programme to achieve its developmental objectives at its expiry in 2015 led to the development and implementation of the Sustainable Development Goals (SDGs) programme commencing 2016. The SDGs progamme has been widely accepted as laudable for its wider approach to global development and sustainability. However, if the SDGs programme is not to end as the Millennium Development Goals did, it is necessary that its implementing actors collaborate with stakeholders of institutions that will make more members of the populace aware of, accepting of, and involved in the implementation of the goals. This is crucial because the goals require the populace' corresponding participation. This paper focuses on one such institutional stakeholder: religious leaders. This paper, through literature review and analysis of surveys and reports, examines the influence religious leaders have on their followers in Africa with Nigeria as a case study. It argues that religious leaders have a strong influence on their followers, as Nigerians and most Africans place more trust in, and respect the opinions of their religious leaders than their political counterparts. The paper, therefore, contends that if the global agenda of the SDGs is to be realised by getting a wider Nigerians to accept and involve in the implementation of the sustainable goals, then, the potential influence of religious leaders should be harnessed.